2022
DOI: 10.1016/j.eatbeh.2021.101581
|View full text |Cite
|
Sign up to set email alerts
|

Disordered eating across COVID-19 in LGBTQ+ young adults

Abstract: Emerging evidence suggests that the COVID-19 pandemic is negatively affecting mental health, especially for sexual and gender minority populations. Relatively little is known about the impact of the pandemic on disordered eating behaviors (DEB) for these populations. The aim of this study is to understand changes in DEB across COVID-19 within an LGBTQ+ sample, with a particular focus on differences across sexual and gender identities, and the impact of social support on these outcomes. In a sample of 830 LGBTQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…The current review also found that Covid-19 stress among SGM individuals is associated with elevated risks of disordered eating behavior and increased perception of weight gain among them ( 33 ). Hart et al ( 49 ) noted that most of their study participants reported an increase in the urge and frequency of engaging in disordered eating behavior. Moreover, they found an association between disordered eating behavior and increased levels of psychological stress due to Covid-19 and the quality of relationships at home and non-acceptance of one's sexual identity by family members.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…The current review also found that Covid-19 stress among SGM individuals is associated with elevated risks of disordered eating behavior and increased perception of weight gain among them ( 33 ). Hart et al ( 49 ) noted that most of their study participants reported an increase in the urge and frequency of engaging in disordered eating behavior. Moreover, they found an association between disordered eating behavior and increased levels of psychological stress due to Covid-19 and the quality of relationships at home and non-acceptance of one's sexual identity by family members.…”
Section: Resultsmentioning
confidence: 98%
“…Out of the 16 studies, seven studies presented a comparative account across heterosexual and SGM respondents ( 5 , 8 , 39 , 32 , 33 , 44 , 46 ), while three more studies included heterosexual respondents although in very small percentages ( 6 , 7 , 49 ). The rest of the studies included only the SGM group for the investigation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations